ANALISIS POTENSI EKONOMI PROVINSI NUSA TENGGARA BARAT TAHUN 2016-2020 - Subhan Purwadinata; Binar Dwiyanto Pamungkas; H Herwansyah (Jurnal Ekonomi & Bisnis, 2021)
This study aims to know the base sector and the potential sector of economy in NTB Province in 2016-2020.The data used in this study was secondary data in form time series data namely Gross Domestic Product (GDP), Gross Regional Domestic Product (GRDP) based on constant prices 2010. The analytical tools used were Locational Quotient (LQ), Shift Share (SS) and Growth Ratio Model (MRP). The results of study showed that there were 9 of base sectors in West Nusa Tenggara Province namely mining and quarrying sector with value index of 2.39, then the health and social activities sector with value index of 1.78 and the agricultural sector with value index of 1.77.While for the potential sectors in West Nusa Tenggara Province (NTB) for the period of 2016-2020, there were 11 potential sectors in which its growth were slow in NTB but it were fast at the national level and there were 3 potential sectors in which its growth were slow at the National level while it were fast in NTB namely the Mining and Quarrying sector,Transportation and Warehousing, and Provision of Accommodation and Food and Drink.